The role of social vitality on the impact of sports activities on public health based on the theory of planned behavior - Elnaz Bahrami; Reza Sabonchi; Gholamreza Khaksari; Homa Naderifar (Sport Sciences and Health Research)
Background: There are relationships between exercise effect on mental health, especially negative emotions such as anxiety and stress.Aim: The aim study was the effect of participation in public sports activities based on the theory of planned behavior on the public health.Methods: This study is a descriptive correlation study with confirmatory factor analysis approach. Data was collected from 288 public sports participants of Tehran Municipality. Three standard questionnaires, including Goldberg General Health (1979) with 28 questions were used for collecting data.Results: Construct Variance extracted was 0.4, composite reliability 0.9 and Cronbach’s Coefficient Alpha 0.7. As a result, the convergence validity and reliability of the model were acceptable. Divergent validity, convergent validity and discriminant validity of the model were confirmed by first order and second order confirmatory factor analyses. The positive validity of all subscriptions for latent variables indicated the appropriate quality of the measurement model. In this model, it was found that regular physical activity combined with planned behavior had a direct effect of 53% (correlation 0.729) on general health.Conclusion: According to the structural equation model, it was found that regular physical activity combined with planned behavior has a direct effect of 58% on general health.